Insights into the dynamics of the 2010 Eyjafjallajökull eruption using seismic interferometry and network covariance matrix analyses - Caudron, Corentin; Soubestre, Jean; Lecocq, Thomas; White, Robert S.; Brandsdóttir, Bryndís; Krischer, Lion (Earth and Planetary Science Letters, 2022)
ISSN:0012-821X ISSN:1385-013X